EFEKTIFITAS STRATEGI KOMUNIKASI PEMASARAN UNIVERSITAS ISLAM SYEKH YUSUF DALAM PENERIMAAN MAHASISWA BARU TAHUN 2022 - Yoman, Mad (Universitas Islam Syekh Yusuf, 2022)
This research is about the effectiveness of marketing communication strategies at the Syekh Yusuf Islamic University (UNIS) in accepting new students in 2022 with the aim to know the marketing communication strategies used are effective or not. The type of research used in this research is descriptive qualitative with a pospositivisme paradigm through interviews, observation and documentation as data collection methods. Researchers describe and implement the existing data in the field. Based on the results of the research, it was found that there was an effectiveness of marketing communication strategies in promotional activities such as school visits, presentations, quality of customer service and social media activities carried out by public relations although there was a slight decrease in the number of new student admissions.